SUPPLEMENTATION WITH VITAMIN D - CURRENT RECOMMENDATIONS - Dimitar B. Marinov; Darina N. Hristova (Peytchinski Publishing, 2021)
Background: Vitamin D (calciferol) is a group of fat-soluble compounds, which are essential for calcium homeostasis, immunomodulation, antiproliferative effects, and more. It can also be viewed as a prohormone. Almost every cell in the human body has a receptor for vitamin D. Its synthesis depends on multiple factors. Review results: Vitamin D deficiency affects almost 50% of the world'spopulation, making it the most common vitamin deficit. There are multiple causes, mostly related to the modern lifestyle and ineffective exposition to the sun. The modern diet also lacks good sources of the vitamin, which makes supplementation the best option for optimal health. Supplements should be administered after serum level tests. Measurements below 20 ng/ml (50 nmol/l) are indication for supplementation. How effective the supplementation is will depend on the type of supplement, individual's genetic factors, and with what foods the supplement is taken with. Dietary reference values for adequate intake and tolerable upper limit should be taken into consideration as well. Serum levels above 30 ng/ml (above 70 nmol/l) are considered optimal for health. There is a risk of toxicity in cases of over-supplementation and serum levels above 150 ng/ml (375 nmol/l). Conclusion: The widespread vitamin D deficiency leads to many public health risks. Supplementation can have a therapeutic effect in many different conditions. To maximize the effect, and reduce the risks of toxicity, an individual assessment of the most appropriate regimen and the dosage of vitamin D supplementation is needed.